THU0264 Impact of extra-articular manifestations on patient-reported outcomes in ankylosing spondylitis and psoriatic arthritis: interim results from the complete studies. (12th June 2018) - Bessette, L.; Khraishi, M.; Florica, B.; Setty, Y.; Teo, M.; Remple, V.
Abstract : Background: Extra-articular manifestations (EAMs) in rheumatic diseases have been previously found to negatively impact health outcomes including quality of life and work capacity. Even though EAMs may be directly associated with worse response to treatment, differences in patient-reported outcomes (PROs) based on the presence of EAMs could be an important contributory variable. Objectives: To assess the impact of EAMs on PROs among patients with active AS or PsA followed in Canadian routine clinical care. Methods: Patients eligible for the COMPLETE studies are anti-TNFα naïve adults, with active AS or PsA per the judgment of the treating physician, who require change in their treatment regimen. In the current analysis patients enrolled between July/2011 - June/2017 were included. EAMs were defined as the presence of the following at baseline: enthesitis, uveitis, inflammatory bowel disease (IBD) or psoriasis (EAMAS1 for AS); enthesitis, uveitis, or IBD (EAMAS2 for AS); enthesitis or dactylitis (EAMPsA for PsA). PROs included the Short Form Health Survey (SF-12), Work Limitations Questionnaire (WLQ) and Beck's Depression Inventory (BDI). PROs were compared between patients with and without EAMs using the independent samples t-test. The independent association between presence of EAMs and PROs at baseline was assessed with multivariate generalised linear models adjusting for disease state (high/very high vs. inactive/low/moderate disease based on the BASDAI for AS and the DAS28 for PsA), disease type, and ever smoking. Results: A total of 609 AS and 406 PsA patients were included with a mean (SD) age of 43.1 (13.4) and 51.3 (12.3) years, respectively. EAMAS1 and EAMAS2 prevalence among AS patients was 33.9% and 25%, respectively, while among PsA patients EAMPsA prevalence was 45.4%. In univariate analysis, presence of EAMs in AS was associated with significantly higher disease activity, BDI total score, WLQ mental interpersonal demands (only for EAMAS1 ), WLQ physical demands, WLQ time demands, SF-12 physical function, SF-12 role physical, SF-12 bodily pain, SF-12 vitality, SF-12 mental health (only for EAMAS1 ), and the SF-12 physical component summary score (PCS). Among PsA patients, patients with EAMPsA had higher disease activity but no significant association was observed between EAMPsA and PROs. Upon adjusting for disease state, disease type, and ever smoking, presence of EAMAS1 /EAMPsA for AS/PsA patients was associated with significantly higher BDI total score (14.0 vs. 12.6, p=0.046) and lower SF-12 physical function (38.4 vs. 44.8, p=0.047). When evaluating the impact of EAMAS2 /EAMPsA for AS/PsA patients no significant differences were observed in PROs; however, BDI was notably higher among patients with EAMs (14.1 vs. 12.7, p=0.056). Conclusions: In a Canadian routine clinical care setting, a substantial proportion of AS and PsA patients requiring a change in treatment report EAMs. Presence of EAMs, particularly psoriasis for AS patients, was found to be a significant independent predictor of depressive symptoms and reduced quality of life due to worse physical functioning. Acknowledgements: JSS Medical Research, Montreal, Canada Disclosure of Interest: L. Bessette Consultant for: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Celgene, Lilly, Novartis, Speakers bureau: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Lilly, Novartis, M. Khraishi Consultant for: AbbVie, Speakers bureau: AbbVie, B. Florica Consultant for: for Roche, Abbvie, Pfizer, Janssen, Celgene, UCB, Speakers bureau: Janssen, Merck, Abbvie, Roche, BMS, Novartis, Y. Setty Consultant for: AbbVie, M. Teo Consultant for: AbbVie, Amgen, Celgene, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi-Genzyme UCB, Speakers bureau: AbbVie, Roche, V. Remple Shareholder of: AbbVie, Employee of: AbbVie